Design and evaluation of siRNA molecules targeting conserved UL15 sequence in the HSV genome: An in silico and in vitro study - Archana Mahadev Rao, Fayaz Shaik Mohammad, Divyashree Mysore Somashekara, Rakesh R. Rahangdale, Sanskruti Shrenik Patil, Raghu Chandrashekhar Hariharapura (Journal of Applied Pharmaceutical Science, 2025)
An alarming increase in the appearance of acyclovir resistance Herpes simplex virus (HSV) strains, has prompted the research community to actively search for new techniques for prevention and treatment of the disease. The targeted gene, ul15, is the most conserved gene in Herpesviridae family and the protein encoded by it is the large subunit for the terminase complex required for viral DNA encapsidation. The use of siRNA targeting ul15 gene product as a therapeutic agent for Herpesvirus infection is not explored. To design siRNA molecules that can target conserved areas of ul15 gene across the different HSV strains and test their antiHSV activity. n this study, siRNA molecules that can block ul15 expression have been designed to control HSV infection. The study has shown that the design of siRNA could be carried out using online web servers like siRNA Pred, siPred, and IDT, wherein the siRNA had the capacity to cause a 10 log reduction in viral load. The specificity, stability, and capacity to inhibit different viral strains were also tested in silico. The antiHSV activity of siRNA and siRNA in combination with acyclovir was verified using in vitro cytopathic effect inhibition (CPE) assay and real time-polymerase chain reaction. The online freeware provided two sequences of siRNA which were conserved across the different strains of HSV and have ~78% inhibition efficiency. The in silico analysis also displayed the capacity of the siRNA molecules to bind the target mRNA spontaneously (−32.9 for siRNA1 and −17.9 kcal/mol for siRNA2). The in vitro CPE assay showed the antiviral activity at 50 nM for siRNA1 was ~50% and for siRNA2 was ~30%. The designed siRNA1 and 2 molecules reduced the viral gene expression to 1.7% and 2%, respectively. The synergistic activity of the siRNA and acyclovir was demonstrated at a concentration of 50 nM and 18 μM, respectively. The study provides a way to reduce the dose of acyclovir required to control the infection, thus reducing its known side effects such as nausea, diarrhea, vomiting, and neurotoxicity. This combination may also help reduce the incidences of developing acyclovir resistance.
Keywords: siRNA, Herpes simplex virus, UL15, RNA interference, in silico design, cytopathic effect inhibition (CPE)